Paulus og stoicismen - Dochhorn, Jan (Dansk Teologisk Tidsskrift, 2012)
Troels Engberg-Pedersen’s Cosmology and Self in the Apostel Paul presents a philosophical exegesis of Paul which reconstructs a materialistic concept of Pneuma as a bodily entity and stresses the nonmetaphorical and concrete bodily meaning of theological, especially pneumatological concepts in the letters of Paul. TEPs theory about the material Pneuma and its Stoic backgrounds is criticised in this review whereas the impact of his focus on the non-metaphorical meaning of Pauline concepts (e.g. church as Christ’s body) should not be underestimated. There is also a general theological potential in his claim that divine and human agency in Paul do not contradict one another.